Analysis and Development of Restrictor for Parallel Twin Engine in FSAE Cars - Vignesh Kumar, M; Murugesan, Sivanesan (International Journal of Engineering and Technology, 2018)
This research aims to the development of intake restrictor of a formula SAE car engine which is of 300cc parallel twin cylinder engine. In this paper we have considered different venturi designs which have different convergence and divergence angles. The main aim is to optimize the pressure and velocity of air which tends to offer better combustion reflects in performance. The parameters which are to be considered for design as well as analysis are mach number, intake velocity, mass flow rate, etc.., To perform this research we have chosen the Ansys fluent software tool and the analytical calculations were made for standard design. It is observed that the continuous variations in converging and diverging angles offers better results in both pressure and velocity characteristics of air entering for combustion.Â